Diagnostic Yield of 2 Strategies for Adult Celiac Disease Identification in Primary Care. Issue 1 (January 2019) - Scoglio, Riccardo; Trifirò, Gianluca; Sandullo, Antonino; Marangio, Giovanni; D'Agate, Cinzia; Costa, Stefano; Pellegrino, Salvatore; Alibrandi, Angela; Aiello, Andrea; Currò, Giovanni; Cuzzupè, Chiara; Comisi, Fabrizio; et al.
Abstract : Goals: To compare the diagnostic yield and cost-consequences of 2 strategies, screening regardless of symptoms versus case finding (CF), using a point-of-care test (POCT), for the detection of celiac disease (CD) in primary care, to bridge the diagnostic gap of CD in adults. Materials and Methods: All subjects under 75 years of age who consecutively went to their general practitioners' offices were offered POCT for anti-transglutaminase immunoglobulin A antibodies. The POCT was performed on all subjects who agreed, and then a systematic search for symptoms or conditions associated with higher risk for CD was performed, immediately after the test but before knowing the test results. The 2 resulting groups were: (a) POCT positive and (b) symptomatic subject at CF. Subjects were defined as symptomatic at CF in the presence of 1 or more symptoms. All POCT-positive or symptomatic subjects at CF were referred to the CD Centers for confirmation of CD. Data on resource consumption were gathered from patients' charts. Cost of examinations, and diagnostic and laboratory tests were estimated with regional outpatient tariffs (Sicily), and a price of [Euro sign]2.5 was used for each POCT. Results: Of a total of 2197 subjects who agreed to participate in the study, 36 (1.6%) and 671 (30.5%) were POCT positive and symptomatic at CF, respectively. The yield from the screening and CF was 5 new celiac patients. The total cost and mean cost for each new CD case were [Euro sign]7497.35 and [Euro sign]1499.47 for the POCT screening strategy, and [Euro sign]9855.14 and [Euro sign]1971.03 for the CF strategy, respectively. Assuming consecutive use of both strategies, performing POCT only in symptomatic subjects at CF, the calculated yield would be 4 new diagnoses with a total cost of [Euro sign]2345.84 and a mean cost of [Euro sign]586.46 for each newly diagnosed patient. Only 1 patient was celiac despite a negative POCT. Conclusions: Testing symptomatic subjects at CF only by POCT seems the most cost-effective strategy to bridge the diagnostic gap of adult CD in primary care.